Postdiagnosis social networks and breast cancer mortality in the After Breast Cancer Pooling Project. Issue 7 (12th December 2016) - Kroenke, Candyce H.; Michael, Yvonne L.; Poole, Elizabeth M.; Kwan, Marilyn L.; Nechuta, Sarah; Leas, Eric; Caan, Bette J.; Pierce, John; Shu, Xiao‐Ou; Zheng, Ying; Chen, Wendy Y.
Abstract : BACKGROUND: Large social networks have been associated with better overall survival, though not consistently with breast cancer (BC)–specific outcomes. This study evaluated associations of postdiagnosis social networks and BC outcomes in a large cohort. METHODS: Women from the After Breast Cancer Pooling Project (n = 9267) provided data on social networks within approximately 2 years of their diagnosis. A social network index was derived from information about the presence of a spouse/partner, religious ties, community ties, friendship ties, and numbers of living first‐degree relatives. Cox models were used to evaluate associations, and a meta‐analysis was used to determine whether effect estimates differed by cohort. Stratification by demographic, social, tumor, and treatment factors was performed. RESULTS: There were 1448 recurrences and 1521 deaths (990 due to BC). Associations were similar in 3 of 4 cohorts. After covariate adjustments, socially isolated women (small networks) had higher risks of recurrence (hazard ratio [HR], 1.43; 95% confidence interval [CI], 1.15‐1.77), BC‐specific mortality (HR, 1.64; 95% CI, 1.33‐2.03), and total mortality (HR, 1.69; 95% CI, 1.43‐1.99) than socially integrated women; associations were stronger in those with stage I/II cancer. In the fourth cohort, there were no significant associations with BC‐specific outcomes. A lack of a spouse/partner ( P = .02) and community ties ( P = .04) predicted higher BC‐specific mortality in older white women but not in other women. However, a lack of relatives ( P = .02) and friendship ties ( P = .01) predicted higher BC‐specific mortality in nonwhite women only. CONCLUSIONS: In a large pooled cohort, larger social networks were associated with better BC‐specific and overall survival. Clinicians should assess social network information as a marker of prognosis because critical supports may differ with sociodemographic factors. Cancer 2017;123:1228–1237. © 2016 American Cancer Society . Abstract : A large, prospective, pooled cohort study of 9267 women with breast cancer shows that women who are socially isolated have higher risks of recurrence, breast cancer–specific mortality, and overall mortality. In analyses of specific ties and outcomes, specific associations differ by age, race/ethnicity, and country of origin, and this suggests that critical supports differ with sociodemographic factors.